Applications of Polyhydroxyalkanoates in the Medical Industry - Brigham, Christopher John; Sinskey, Anthony J. (International Journal of Biotechnology for Wellness Industries, 2012)
The bio-based, biodegradable family of polymers, polyhydroxyalkanoates (PHA), is an attractive candidate for an environmentally friendly replacement of petroleum-based plastics in many applications. In the past decade, many groups have examined the biodegradability and biocompatibility of PHA in cell culture systems or in an animal host. Findings suggest that PHA is a suitable material for fabrication of resorbable medical devices, such as sutures, meshes, implants, and tissue engineering scaffolds. The degradation kinetics of some PHA polymers is also suggestive of drug release applications. In this review, we examine the progress, potential applications, challenges and outlook in the medical polyhydroxyalkanoate field.